2022
DOI: 10.1161/jaha.121.022854
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and Cardiac Outcomes in Pediatric Dilated Cardiomyopathy

Abstract: Background Pediatric dilated cardiomyopathy (DCM) is a well‐known clinical entity; however, phenotype–genotype correlations are inadequately described. Our objective was to provide genotype associations with life‐threatening cardiac outcomes in pediatric DCM probands. Methods and Results We performed a retrospective review of children with DCM at a large pediatric referral center (2007–2016), excluding syndromic, chemotherapy‐induced, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Controversial study results have been obtained with pediatric DCM. TTN and MYH7 mutations were identified as predominant in a cohort of 106 pediatric patients [74]. In another study analyzing 36 patients, only one TTN mutation, a truncation (p.Arg33703*), was identified in a 16-year-old male DCM patient [108].…”
Section: Sarcomeric Dysfunctionmentioning
confidence: 97%
See 2 more Smart Citations
“…Controversial study results have been obtained with pediatric DCM. TTN and MYH7 mutations were identified as predominant in a cohort of 106 pediatric patients [74]. In another study analyzing 36 patients, only one TTN mutation, a truncation (p.Arg33703*), was identified in a 16-year-old male DCM patient [108].…”
Section: Sarcomeric Dysfunctionmentioning
confidence: 97%
“…DCM based on genetic defects seems to form the main cause of pediatric DCM, whereby the vast majority of gene mutations is found in sarcomeric proteins, especially in MYH7, TTN, TNNT2, TPM1, MYBPC3, MYL2, TNNC1 (Troponin C), and ACTN2. Others are found in LMN, DES, VCL (Vinculin), TTR (transthyretin), BAG3 (associated with apoptosis), MT-TS2 (encoding a mitochondrial small RNA), or transcription factor encoding PRDM16 [74][75][76][77][78]. In adult and pediatric DCM, the same genes seem to be affected, though unfortunately, most genetic testings have been performed in adults [79].…”
Section: Cellular Compartments Affected By Genetic Mutations Causing ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Out of these 15 genes, 9 genes ( MYH7 , SCN5A , TNNT2 , LMNA , MYBPC3 , MYH6 , TNNC1 , TNNI3 and TPM1 ) are also known to cause DCM in adults. Recently, Khan et al [ 30 ] did a cohort study on 109 pediatric patients and found that TTN (Titin) truncation was the most prevalent cause of genetic DCM in pediatric patients. Along with TTN tv, genetic variations (mutation) were also detected in MYH7 among pediatric DCM patients.…”
Section: Causes Of Dcmmentioning
confidence: 99%
“… 17 To date, DCM‐causing variations in >250 genes have been implicated with the development of DCM, of which the vast majority code for sarcomere proteins, nuclear envelope proteins, cytoskeleton proteins, Z‐band proteins, intercalated disc proteins, ion channel proteins, gap junction channel proteins, RNA‐binding proteins, mitochondrial proteins, and transcriptional factor proteins. 1 , 2 , 3 , 4 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 Additionally, genome‐wide association studies have led to the discovery of many new common variants involved in DCM, in addition to novel rare variants involved in DCM. 33 Nevertheless, the genetic architecture of DCM is highly complex and diverse owing to pronounced genetical heterogeneity, and the genetic determinants underpinning DCM in a large proportion of cases remain to be identified.…”
mentioning
confidence: 99%